Isaiah L. Kephart’s Letter to Horace Kephart, September 2, 1888 - Ashburn, Aria Rose (2019)
This edition is created from the manuscript of I. L. Kephart’s letter to Horace Kephart on September 2, 1888. Within this this letter, I. L. Kephart lays out the Kephart family tree in what is a rudimentary genealogy of the paternal side of Horace’s family, seemingly at Horace’s request. In addition, Isaiah recounts to Horace he was invited to Clearfield County, Pennsylvania to preach at a “campmeeting,” or church meeting, with all of the expenses paid by the church. Afterwards, he writes a few brief paragraphs on how Horace’s family in Massachusetts is doing, and discusses briefly the upcoming election, before signing off. The genealogy continues to be a subject in subsequent letters; Isaiah continues the story of the family lineage in a letter he wrote to Horace in October of the same year. Isaiah is Horace Kephart’s father, and seems to be deriving this genealogy from his memory and information he has received from other members of the Kephart family.